Lost at sea : the Jon Ronson mysteries - Ronson, Jon, 1967- (Riverhead Books, 2012)
Ronson investigates the strange things we are willing to believe in, from lifelike robots programmed with the personalities of our loved ones to indigo children to hyper successful spiritual healers. He looks at ordinary lives that take on extraordinary perspectives, for instance a pop singer whose greatest passion is the coming alien invasion, and the scientist designated to greet those aliens when they arrive. Ronson throws himself into the stories. In a tour de force piece, he splits himself into multiple Ronsons (Happy, Paul and Titch, among others) to get to the bottom of predatory tactics of credit card companies and the murky, fabulously wealthy companies behind those tactics. Amateur nuclear physicists, assisted-suicide practitioners, the town of North Pole, a Christmas-induced high school mass-murder plot, Ronson explores all these tales with a sense of higher purpose and universality, and suddenly, mid-read, they are stories not about the fringe of society or about people far removed from our own experience, but about all of us.